A Novel Custom Cycle Ergometer Protocol to Determine V?O2max: Validation with ACSM`s Cycle Ergometry Metabolic Equation - Lankford, D. M.; Cummings, D. M. (Exercise, Sport, and Movement, 2023)
Introduction Protocols for determination of maximal oxygen consumption (VO2max) on a cycle ergometer should be easily administered while maximizing physiological efficiency and minimizing premature local muscle fatigue for individuals of variable fitness levels. Current protocols typically increase workload by adding resistance to the flywheel; however, increasing pedal rate later in the test, rather than resistance, may provide increased physiological efficiency, yielding a more valid determination of VO2max.